Perbandingan Kinerja dari Beberapa Alat dan Mesin Ekstraksi Santan Kelapa di Manokwari - Wilson Palelingan Aman (Agritechnology, 2022)
Coconut milk is one of the main products of the coconut plant. The coconut milk extraction process carried out by the community so far is done manually, by adding water to the grated coconut, then squeezing it to remove the coconut milk, then filtering it so that it is separated from the dregs. This method reportedly still leaves quite a lot of oil in the dregs. In addition, there is quite a lot of water that must be evaporated in the cooking process. The more water content in coconut milk, the more energy needed to evaporate. Research on coconut milk extraction using a combination of tools and machines has been carried out in Manokwari. The purpose of this study was to determine the effect of using different extraction methods and equipment on the performance of coconut milk extraction results. Parameters for measuring the extraction performance of the tools and machines used are the coconut milk extraction capacity, the yield of coconut milk produced, and the yield of coconut milk in dregs. The research method used is experimentation by testing several tools in the coconut milk extraction process. The results showed that based on the parameters of coconut milk extraction capacity and the yield of coconut milk produced, the best treatment in this study was a combination of grating and extraction with a 50 ton hydraulic jack, with an extraction capacity of 9.64 l/hour and a yield of coconut milk of 62.80%. Meanwhile, the grating and screw extraction treatments showed the best results based on the parameters of the yield of coconut milk in dregs, namely 23.76%. From the results of the research conducted, as a whole it can be concluded that the best method for coconut milk extraction is a combination of grating and hydraulic type pressing.